2007
DOI: 10.1155/2007/289059
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence of Hepatitis E Virus Infection in an Indigenous North American Population

Abstract: The results of the present study showed that serological evidence of HEV infection was present in 3% of the observed Canadian Inuit population; the presence of IgM anti-HEV suggested recent infection and HEV did not appear to coinfect with other common hepatotropic viruses. The source of HEV infection in the population remains unclear. These findings are interesting but preliminary. Additional data are required to determine whether HEV infections are responsible for otherwise unexplained acute hepatitis in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 17 publications
1
27
0
1
Order By: Relevance
“…A prevalence of 3% for hepatitis E virus (HEV) amongst Canadian Inuit within the Arctic region was reported [140]. Consumption of deer meat has been reported to transmit HEV, via fecal-oral route.…”
Section: Discussionmentioning
confidence: 99%
“…A prevalence of 3% for hepatitis E virus (HEV) amongst Canadian Inuit within the Arctic region was reported [140]. Consumption of deer meat has been reported to transmit HEV, via fecal-oral route.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that sporadic infection occurs through a zoonotic route and is not limited to developing countries. Seroprevalence suggests hepatitis E infection may also be prevalent in high-income countries (21), such as the United States (17), the United Kingdom (3), and Japan (18). The overall mortality rate of HEV infection during an outbreak generally ranges from 1 to 15%, and the highest mortality occurs in pregnant women, with fatality rates of up to 30% (19).…”
mentioning
confidence: 99%
“…However, a recent study showed that 3% of a population of Canadian Inuit had IgG antibodies to HEV (none were viremic). HEV infection has been linked to consumption of deer and caribou, although local caribou were all HEV-negative in this study [45] .…”
Section: Hepatitis D and Ementioning
confidence: 58%